Pengaruh Kondisi Proses Terhadap Kuat Tarik Pulp Pada Pembuatan Pulp Rumput Perimping Dengan Pelarut Organik Asam Formiat - Susanto, Edi; Helwani, Zuchra; Zulfansyah, Zulfansyah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Perimping grass is one of lignocellulosic material which has not been fully utilized, so it is potential to be used as raw material for pulping which will provide economic value added. Organosolv pulping is the process of pulp making using organic solution. The objectives of this research is to study effect of the process conditions on tensile index. Effect of the process conditions were studied by Response Surface Methodology (RSM) with Central Composite Design (CCD). The experiment pulping is carried out at the boiling temperature of liquor at atmospheric pressure, with 40 grams of perimping grass using formic acid (concentrations of 60%, 70%, and 80%), reaction time (60 minutes, 120 minutes, and 180 minutes), liquid to solid ratio (10/1, 15/1 , And 20/1 b/b), with HCl catalyst 0.1% wt. The result pulp of the perimping grass for tensile index is 659.3-2.1149 N m/g. The variable interaction (concentration of formic acid and reaction time) is a significant factor to the pulp tensile index.Keywords: formic acid, organosolv pulping, perimping grass, RSM, tensile index